Pengaruh pembelajaran think-talk-write terhadap kemampuan komunikasi matematik dan sikap positif siswa terhadap matematika - Habeahan, Winmery Lasma; Sitio, Hetdy; Wahyuni, Fitry (Mahesa Research Center, 2021)
The purpose of this study was to determine whether the mathematical communication skills and attitudes of students who were taught with the Think-Talk-Write (TTW) strategy were better than conventional learning. This research is a quasi-experimental research which compares two learning models, namely the TTW cooperative learning model and the conventional learning model. This research was conducted on students of class VII SMPS Mentari Bangsa Medan, which consisted of 2 classes. This study involved two variables, namely the independent variable and the dependent variable. The independent variable is the TTW and KAM learning strategy, while the dependent variable is the mathematical communication skills and attitudes of students towards learning. The sample consist of 42 students for TTW strategy and 37 students for conventional learning. The conclusion is that students who get learning with the TTW strategy have significantly better mathematical communication skills than students who get conventional learning (tcount = 4,93 more than ttable =1,66) and the attitudes of students who get learning with the TTW strategy are significantly better than students who get conventional learning (tcount = 3,14 more than ttable = 1,66).